Aminoribosylated Analogues of Muraymycin Nucleoside Antibiotics - Wiegmann, Daniel (Molecules, 2018)
Nucleoside antibiotics are uridine-derived natural products that inhibit the bacterial membrane protein MraY. MraY is a key enzyme in the membrane-associated intracellular stages of peptidoglycan biosynthesis and therefore considered to be a promising, yet unexploited target for novel antibacterial agents. Muraymycins are one subclass of such naturally occurring MraY inhibitors. As part of structure-activity relationship (SAR) studies on muraymycins and their analogues, we now report on novel derivatives with different attachment of one characteristic structural motif, i.e., the aminoribose moiety normally linked to the muraymycin glycyluridine core unit. Based on considerations derived from an X-ray co-crystal structure, we designed and synthesised muraymycin analogues having the aminoribose attached (via a linker) to either the glycyluridine amino group or to the uracil nucleobase. Reference compounds bearing the non-aminoribosylated linker units were also prepared. It was found that the novel aminoribosylated analogues were inactive as MraY inhibitors in vitro, but that the glycyluridine-modified reference compound retained most of the inhibitory potency relative to the unmodified parent muraymycin analogue. These results point to 6′-N-alkylated muraymycin analogues as a potential novel variation of the muraymycin scaffold for future SAR optimisation.